Employing Watermelon rind, Polyurethane Sponges, and Cotton fibers as Bio-carriers - mohammed mansour (Waste Technology, 2021)
Water scarcity in Egypt is a critical issue that threats all the life fields such as industry and agriculture sectors. So, searching for alternative water resources was the key solution by depending on treating dairy wastewater in order to provide sufficient treated water enough to reuse in other fields. Integrated fixed film activated sludge process (IFAS) was employed as a biological treatment process. A laboratory pilot was established as a simulation of the biological treatment process. The laboratory pilot consists of primary sedimentation tank, aeration tank, and final settling tank with dimensions of 50 × 25× 25 cm for each. Three bio-carriers were used as IFAS Media with different filling ratio in order to achieve COD, BOD, TN, and TP removal efficiency. Watermelon rind was used in the first experimental trial, then Polyurethane sponges in the second experimental trial, and Cotton fibers in the third experimental trial. After analyzing the physicochemical characteristics of dairy wastewater samples, it was clear that Cotton fibers was the most effective in removing BOD, BOD, TN, and TP concentrations with removal efficiency of  88.35%, 88.3%, 76 %, and 69.3% respectively.